On the synthesis of optimum monopulse antenna array distributions - McNamara, Derek Albert (Department of Electrical Engineering, 2016)
The stringent specifications of modern tracking systems demand antennas of high performance. For this reason arrays are finding increasing application as monopulse antennas. A new exact procedure is introduced for the synthesis of optimum difference distributions for linear arrays of discrete elements, with a maximum sidelobe level specification. The method is based on the Zolotarev polynomial, and is precisely the difference mode equivalent of the Dolph-Chebyshev synthesis for sum patterns. When the interelement spacings are a half-wavelength or larger the element excitations are obtained in a very direct manner from the Chebyshev series expansion of the Zolotarev polynomial. For smaller spacings, a set of recursive equations is derived for finding the array excitation set. Efficient means of performing all the computations associated with the above procedure are given in full. In addition, a set of design tables is presented for a range of Zolotarev arrays of practical utility. A novel technique, directly applicable to arrays of discrete elements, for the synthesis of high directivity difference patterns with arbitrary si delobe envelope tapers is presented. This is done by using the.Zolotarev space factor zeros and correctly relocating these in a well-defined manner to effect the taper. A solution to the direct synthesis of discrete array sum patterns with arbitrary sidelobe envelope tapers is introduced. In this case the synthesis is also done by correct placement of the space factor zeros. The above techniques enable high excitation efficiency, low sidelobe, sum and difference pat terns to be synthesized independently. Contributions to the simultaneous synthesis of sum and difference patterns, subject to specified array feed network complexity constraints, are also given. These utilise information on the excitations and space factor zeros of the independently optimal solutions, along with constrained numerical optimisation. The thesis is based on original research done by the author, except where explicit reference is made to the work of others.